On the place and the genius of the place - Rappaport, Alexander (project baikal, 2023)
The ‘place’ category in architectural theory is in opposition to the ‘space’ category, but ‘place’ is also understood as ‘space’.  It is no coincidence that topology is called the analysis of place. Geometry and topology have had a strong effect not only on physics, crystallography and molecular chemistry, but also on architecture and other humanities, in particular on the psychology of visual perception. “Topophilia” by Yi-Fu Tuan is a bridge that creates the possibility of moving from mathematics and topology to the humanities. However, the use of the concepts of ‘place’ and ‘genius of place’ in the humanitarian sphere in general and in architecture in particular remains at the level of sentimental mythology and phenomenology. Introducing the understanding of the value of place and ‘genius loci’ into the mass consciousness is impossible without rituals related to the life and death of architecture.
Keywords: Place; space; topology; topophilia; genius of place; ritual